Cervical pessary for short cervix in high risk pregnant women: 5 years experience in a single centre. (17th April 2020) - Ivandic, Jelena; Care, Angharad; Goodfellow, Laura; Poljak, Borna; Sharp, Andrew; Roberts, Devender; Alfirevic, Zarko
Abstract: Purpose: To describe single center clinical experience with cervical pessary used for high-risk pregnant women who also had short cervix. We have focused on the techniques to optimize efficacy and minimize the risk of complications and side effects related to pessary insertion, removal, and pregnancy management. Methods: This is an audit from specialist preterm birth prevention clinic in Liverpool Women's Hospital, United Kingdom for the period between January 2013 and December 2017. We also conducted postal survey in November 2015 to evaluate women's experience with vaginal pessary. Results: Out of 235 women who were treated for short cervix, 129 (55%) had cervical pessary as a first line treatment. Overall, 50% of treated women reached term. 17 women (13%) needed additional treatment, 9 women had pessary reinserted (7%), and 53 (41%) had pessary removed before 36 weeks, mainly due to ruptured membranes. Significant vaginal discharge and pelvic discomfort were reported by 14 and 7% women, respectively. 89% of treated women would recommend the pessary treatment to others. Conclusions: Whilst the cervical pessary continues to be evaluated in clinical trials, our experience suggests that pessary is quite easy to insert and remove and is well tolerated by the women.